Genetic Cardiomyopathies: The Lesson Learned from hiPSCs - My, Ilaria (J Clin Med, 2021)
Genetic cardiomyopathies represent a wide spectrum of inherited diseases and constitute an important cause of morbidity and mortality among young people, which can manifest with heart failure, arrhythmias, and/or sudden cardiac death. Multiple underlying genetic variants and molecular pathways have been discovered in recent years; however, assessing the pathogenicity of new variants often needs in-depth characterization in order to ascertain a causal role in the disease. The application of human induced pluripotent stem cells has greatly helped to advance our knowledge in this field and enabled to obtain numerous in vitro patient-specific cellular models useful to study the underlying molecular mechanisms and test new therapeutic strategies. A milestone in the research of genetically determined heart disease was the introduction of genomic technologies that provided unparalleled opportunities to explore the genetic architecture of cardiomyopathies, thanks to the generation of isogenic pairs. The aim of this review is to provide an overview of the main research that helped elucidate the pathophysiology of the most common genetic cardiomyopathies: hypertrophic, dilated, arrhythmogenic, and left ventricular noncompaction cardiomyopathies. A special focus is provided on the application of gene-editing techniques in understanding key disease characteristics and on the therapeutic approaches that have been tested.